Rearing Room Affects the Non-dominant Chicken Cecum Microbiota, While Diet Affects the Dominant Microbiota - Ludvigsen, Jane; Svihus, Birger; Rudi, Knut (Frontiers in Veterinary Science, 2016)
The combined effect of environment and diet in shaping the gut microbiota remain largely unknown. This knowledge, however, is important for animal welfare and safe food production. For these reasons we determined the effect of experimental units on the chicken caecum microbiota for a full factorial experiment where we tested the combined effect of room, diet and antimicrobial treatment. By Illumina Deep sequencing of the 16S rRNA gene, we found that diet mainly affected the dominant microbiota, while the room as a proxy for environment had major effects on the non-dominant microbiota (p=0.006, Kruskal Wallis test). We therefore propose that the dominant and non-dominant microbiotas are shaped by different experimental units. These findings have implications both for our general understanding of the host-associated microbiota, and for setting up experiments related to specific targeting of pathogens.